Social theory and trauma. (February 2013) - Eyerman, Ron
Using the example of three significant social theory texts, Horkheimer and Adorno's Dialectic of Enlightenment, Freud's Moses and Monotheism and Bauman's Modernity and the Holocaust, this article illustrates the difference between personal, collective and cultural trauma. The aim is also to illustrate how personal trauma can impact the construction and representation of social theory.